2008
DOI: 10.1590/s0034-89102008000800011
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças no âmbito da testagem anti-HIV no Brasil entre 1998 e 2005

Abstract: OBJECTIVE:To analize changes in HIV testing, reasons reported by those who were tested or not and received counseling. METHODS:Cross-sectional studies conducted in both men and women aged 16 to 65 years based on representative samples of urban Brazil in 1998 (n=3,600) and 2005 (n=5,040). Sociodemographic, sexual, reproductive characteristics, life experiences and health data were collected and analyzed. Potential differences in the distribution of variables was analyzed using Pearson's chi-square and design-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
(35 reference statements)
0
11
0
3
Order By: Relevance
“…[911] Since one quarter of all HIV tests performed in Brazil are conducted at blood centers, these findings further indicate that alternative testing sites are currently under-utilized by large numbers of persons wishing to know their HIV serostatus. [8]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[911] Since one quarter of all HIV tests performed in Brazil are conducted at blood centers, these findings further indicate that alternative testing sites are currently under-utilized by large numbers of persons wishing to know their HIV serostatus. [8]…”
Section: Discussionmentioning
confidence: 99%
“…[412] Previous studies have shown that many at-risk individuals get tested for HIV for the first time through the blood donation process. [48] This test-seeking behavior may pose a threat to the safety of the blood supply through a small but real risk of donation during the HIV window period. [3] The window period is the length of time following infection before the antibody screening test becomes reactive, which may be few days to a several weeks depending on the testing technology being used (e.g., antibodies are typically detected within three weeks after infection, HIV-RNA in seven to eleven days, p24 antigen in three to ten days after HIV-RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Truly the greatest challenge to stemming the epidemic continues to be reducing the number of undiagnosed infections in the difficult to reach and most vulnerable populations who test too infrequently 18 . Reducing the number of undiagnosed infections is the first step in expanding care and treatment, viral suppression, and ultimately in preventing subsequent infection to new partners 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Current rates of HIV testing among MSM, however, are not commensurate with their risk. While MSM test at higher rates than heterosexual men, they test less frequently than reproductive age women 18 . In a recently conducted 10 city respondent driven sampling study, just over half of the MSM interviewed had never been tested and close to 50% of those who consented to HIV testing and were seropositive were unaware of their infection 3 .…”
Section: Introductionmentioning
confidence: 95%
“…In Brazil, this inequality is evidenced, in part, by HIV testing rates. In a home-based study conducted in Brazil in 2005 [39], the social segments in which the HIV testing rate was found to be lowest among men (28%) and among individuals ≥ 45 years of age (21%), whereas that rate was above the national average (of 34%) among women (38%), especially among those in the 25–34 year age bracket (60%). This is primarily attributable to prenatal HIV testing.…”
Section: Discussionmentioning
confidence: 99%